THE IMPACT OF THE 4th INDUSTRIAL REVOLUTION ON THE EMPLOYMENT RELATIONSHIP AND ADAPTIVE SKILLS REQUIREMENTS (The Pretoria Student Law Review, 2021)
This article reflects on the possible future of labour law as a response to industrialisation, particularly the 4IR. First, I discuss the origin of the industrial revolution by reflecting on the first three industrial revolutions and the present 4IR. Second, I reflect on; 1) the possible impact of the 4IR on the employment relationship and 2) the new and/or adaptive skills requirements. Third, I present recommendations to respond to the fast-changing pace of labour and industrialisation suggested by the World Economic Forum (WEF). I thereafter conclude that the 4IR may be used as a vehicle to promote a socially affirmative interpretation of fairness in the labour context. This promotes a constitutional obligation to protect the interests of workers, in light of technological advancement, that have the potential to widen the income inequality gap.
Keywords: labour; 4IR; protect the interests of workers; constitutional obligation; future of labour law